2010
DOI: 10.1097/meg.0b013e32832c61d7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endoscopic submucosal dissection in elderly patients with early gastric cancer

Abstract: En-bloc and complete resections were achieved less frequently in elderly patients, but the long-term outcomes in elderly EGC patients may be excellent, and ESD is a feasible treatment in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 24 publications
(50 reference statements)
12
73
1
3
Order By: Relevance
“…When histological evaluation was difficult, or, revealed that a lesion was outside the indication criteria and/or that it had a positive margin, the curability was defined as noncurative hospital stay (on post-ESD day 10). The complication rate (bleeding and perforation) was similar to those in other reports [2][3][4][5][6][7][8][9][10], showing that ESD was mostly safely performed even in the elderly. Curative ESD was achieved in 366 of 470 lesions (77.9%).…”
Section: Early Outcomessupporting
confidence: 88%
See 2 more Smart Citations
“…When histological evaluation was difficult, or, revealed that a lesion was outside the indication criteria and/or that it had a positive margin, the curability was defined as noncurative hospital stay (on post-ESD day 10). The complication rate (bleeding and perforation) was similar to those in other reports [2][3][4][5][6][7][8][9][10], showing that ESD was mostly safely performed even in the elderly. Curative ESD was achieved in 366 of 470 lesions (77.9%).…”
Section: Early Outcomessupporting
confidence: 88%
“…The expected survival was based on that of persons of similar age, gender, and calendar year of birth, using life tables for death from all causes for Japan [15] Discussion According to the fiscal 2008 statistics published by the Ministry of Health, Labour and Welfare, the mean life spans in Japan for men and women, respectively, were 79 and 86 years, and the mean life expectancies at the age of 80 years were 8 and 11 years for men and women, respectively [16]. With the coming of such a superaging era, endoscopic treatment has been increasingly performed for EGC in the elderly, and it has been established as a safe and minimally invasive technique [6][7][8][9][10]. However, only one report has been published on the long-term outcomes of endoscopic treatment for EGC in a large number of patients of advanced age [17].…”
Section: Long-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Age was not identified as a risk factor in most studies, with only 1 study reporting that younger patients may be at higher risk for PPB. 34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB.…”
Section: Risk Factors For Ppbmentioning
confidence: 98%
“…Hemorrhage is a complication in 10%-20% of ESDs [3] and perforation in 5% [4] ; most of these cases can be overcome, however, through skilled execution of the endoscopic procedure [5] . The en bloc resection rate for EGC is nearly 80%, depending on the location and size of the lesion; such resection prevents recurrence of the cancer in nearly all cases [6,7] . These data were collected at large-scale hospitals for the preparation of ESD educational curricula and primarily include pro-cedures performed with ample access to the most advanced equipment, skillful endoscopy care teams and gastrointestinal specialists.…”
Section: Introductionmentioning
confidence: 99%